Strategi Personal Selling dalam Meningkatkan Volume Penjualan pada Perusahaan Marketing - Alma Sri Anjani; Budi Hartono (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine the personal selling strategy in increasing sales volume at the DT Group Advertising company. This type of research uses descriptive qualitative and interviews, documentation and information collection through observation as the actual data collection method so as to facilitate the processing of research data. The results of the discussion of personal selling strategies in increasing sales volume at marketing companies are about how to increase sales volume by providing direction to marketing staff and providing material on personal selling, besides that there are steps that marketing staff can take to attract consumers to buy, and giving reawed and punishment for their sales.